Explanatory Models of Local Demarinen Illness in Tegal, Central Java - Nafisah, Jazilatun; Husain, Fadly (Indonesian Journal of Medical Anthropology, 2025)
Demarinan is a local illness resulting from the reconstruction of Javanese culture. The people of Ketanggungan village refer to Demarinen as an illness resulting from an energy imbalance between pregnant women and children. This paper explores Demarinen using Arthur Kleinman’s explanatory model, which helps analyze how people explain the causes, symptoms, changes in body functions, impacts, and treatments chosen to treat Demarinan. The research was conducted using a qualitative and descriptive approach. The results showed that Demarinen is an illness that affects children under or at zero to two years, with the characteristic of children becoming cranky. Although there is a hereditary pathway in diagnosing the illness, Demarinen is not an illness resulting from genetic predisposition but rather a result of social, cultural, and local beliefs by a community group. By understanding how the community interprets the disease through explanatory models, more effective, culturally-based, and accessible health strategies can be developed to improve the community’s overall health.